PREDICTIVE FACTORS OF SUCCESSFUL MICRO-DISSECTION TESTICULAR SPERM EXTRACTION IN NON-OBSTRUCTIVE AZOOSPERMIA - Ahmed Mahmoud Hassan , Osama Ahmed Mohammed , Omar Mohamed Elsoghier , Hafez Badawy Hafez Mohammed , Gamal Abdel Hammid Elsagheer (Chelonian Research Foundation, 2024)
The absence of spermatozoa in semen analysis is a sign of non-obstructive azoospermia (NOA), which is caused by either inadequate or nonexistent generation of fully mature spermatozoa inside the testicles. For individuals with non-obstructive azoospermia, testicular microdissection (TESE) is acknowledged as a safe and successful technique, irrespective of the many underlying causes and preoperative assessments. Hormone levels, age, and the size of the testicles are not reliable markers of the success of a micro-TESE. In males with NOA, especially those who have had several failed biopsies, successful sperm retrieval through microdissection TESE is frequently achievable. Additionally, diagnostic biopsy can provide valuable insights into the likelihood of obtaining sperm during the microdissection TESE procedure.